Experimental evidence of a bubble-merger regime for the Rayleigh-Taylor Instability at the ablation front. (May 2016) - Casner, A; Liberatore, S; Masse, L; Martinez, D; Haan, S W; Kane, J; Moore, A S; Seugling, R; Farrell, M; Giraldez, E; Nikroo, A; Smalyuk, V A; et al.
Abstract: Under the Discovery Science program, the longer pulses and higher laser energies provided by the National Ignition Facility (NIF) have been harnessed to study, first time in indirect-drive, the highly nonlinear stage of the Rayleigh-Taylor Instability (RTI) at the ablation front. A planar plastic package with pre-imposed two-dimensional broadband modulations is accelerated for up to 12 ns by the x-ray drive of a gas-filled gold radiation cavity with a radiative temperature plateau at 175 eV. This extended tailored drive allows a distance traveled in excess of 1 mm for a 130 μ m thick foil, a factor 3x larger than previously achieved on other laser facilities. As a consequence, we have measured the ablative RTI in transition from the weakly nonlinear stage up to the deep nonlinear stage for various initial conditions. A bubble merger regime has been observed and the ablative stabilization strength varied by changing the plastic dopant from iodine to germanium.